Sadistic Sexual Crimes Against Children: Comparing the Manifestation of Sexual Sadism and Crime-Commission Process - Reale, Kylie S. (International journal of offender therapy and comparative criminology, 2024)
Individuals who commit sexual offenses against children have been shown to be distinctive from adult offenders across both individual and crime characteristics. However, an examination of the literature shows that there are gaps in the research related to whether sadism manifests differently between those who target child compared to adult victims. The current study therefore aimed to explore the differences in the characteristics, crime-commission process, and the dimensions of sadism between sadistic crimes of children (n = 101) compared to those of adults (n = 433). Sexual sadism was assessed with the Sexual Sadism Scale (SeSaS) and binary logistic regression analysis and multidimensional scale analysis (MDS) were performed to examine differences between these two groups. Our results showed that sadistic fantasies manifested into four dimensions for both adult and child victims. In terms of differences, sadistic sexual offenses involving children appear to be reflective of deviant fantasies related to overlapping paraphilias (e.g., sadism and pedophilia). Conversely, sadistic crimes involving adult victims involve a crime-commission process that involves a greater degree of structure to control their adult victim and decrease their risk of identification. Implications for clinical assessment and police investigations are discussed.